2006
DOI: 10.1007/s10560-006-0077-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Services Provided for Physically Abused Children: A Four-Year Follow-Up Study in Sweden

Abstract: This paper examines contacts that Swedish physically abused children have with the Department of Social Services (DSS) 4 years after a physical abuse incident has been reported to the police. The children's files have been investigated in an effort to evaluate which child and parent characteristics led DSS to make interventions for the 69 children still in need of assistance, 4 years after the original abuse incident. Intervention by the DSS prior to the reported abuse incident increased the odds 18 times that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In Sweden, research has shown that children who experience parental physical abuse often continue to live with their parents, even after the abuse has come to the attention of the child welfare service (Lindell and Svedin 2006). Despite this, there has been a lack of specialised intervention for this group of families.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, research has shown that children who experience parental physical abuse often continue to live with their parents, even after the abuse has come to the attention of the child welfare service (Lindell and Svedin 2006). Despite this, there has been a lack of specialised intervention for this group of families.…”
Section: Introductionmentioning
confidence: 99%
“…Children often continue to reside with their parent(s) after physical abuse has been disclosed (Lindell & Svedin, 2006). Previous research has revealed insufficient results for actions taken by Child Welfare Service after referrals of child physical abuse.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…Re-referrals and renewed reports of abuse to Child Welfare Service can be due to noneffective interventions given in the first place (cf. Jonson-Reid et al, 2003; Heimer et al, 2017a; Lindell & Svedin, 2006). Different parenting programs may offer some general support to this population.…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
See 2 more Smart Citations